Recolha de contratos de despesa pública e segmentação dos perfis de despesa a nível municipal - Freire, Filipe Manuel Leitão Gonçalves (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence